2008
DOI: 10.1007/s00034-008-9025-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Watermarking for Zerotree-Based Applications

Abstract: An optimized scheme for watermarking based on zerotrees is proposed in this paper. Digital watermarking is an effective means for protecting copyrights with three of the most fundamental requirements: watermark imperceptibility, watermark robustness, and watermark capacity. Conventional techniques in the literature mainly perform watermark embedding and extraction processes in the transform domain, including the discrete Fourier transform, discrete cosine transform, and discrete wavelet transform domains. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…The crossover operator of a real-coded GAs is performed by the borrowing concept of convex combination. The random mutation operator is used to change the gene with a random number in the problem's domain [34,35].…”
Section: Genetic Algorithmsmentioning
confidence: 99%
“…The crossover operator of a real-coded GAs is performed by the borrowing concept of convex combination. The random mutation operator is used to change the gene with a random number in the problem's domain [34,35].…”
Section: Genetic Algorithmsmentioning
confidence: 99%
“…For measuring imperceptibility, we use PSNR of watermarked image to serve as an objective measure. In evaluating robustness, after applying some deliberate attacks Chu et al 2008), we calculate the BCR. For measuring capacity, we count the average number of bits, C, embedded into one 8 × 8 block, since we are going to embed the watermark with discrete cosine transform (DCT).…”
Section: Relationships Among Watermarking Requirementsmentioning
confidence: 99%
“…The genetic algorithm (GA) has been used plentifully in information hiding discipline these years (Chu et al 2008;Huang et al 2007;Pan et al 2004) and has been shown to be an effective technique for improving the performance of information hiding systems. For example, the GA is helpful to select proper zerotrees in a wavelet transform for a watermark system (Chu et al 2008), select proper frequency coefficients to carry watermark , and overcome the VQ index assignment problem in VQ-based watermark systems to make them suitable for transmitting the watermarked image over noisy channels (Pan et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the GA is helpful to select proper zerotrees in a wavelet transform for a watermark system (Chu et al 2008), select proper frequency coefficients to carry watermark , and overcome the VQ index assignment problem in VQ-based watermark systems to make them suitable for transmitting the watermarked image over noisy channels (Pan et al 2004). …”
Section: Introductionmentioning
confidence: 99%